Redefinition of Parkinson’s Disease - Schäffer, Eva; Berg, Daniela (Neurology International Open, 2017)
In 2015, a working group of the International Parkinsonʼs and Movement Disorders Society (MDS) presented new clinical diagnostic criteria for Parkinsonʼs disease (PD). This review outlines the key insights with regard to pathophysiology, various clinical manifestations and clinical progression which form the basis for a redefinition and the new, summarized clinical diagnostic criteria of Parkinson’s disease. Essential findings, which led to the new diagnostic criteria, include (i) the recognition of the importance of non-motor symptoms, which may have a tremendous influence on the quality of life of patients and have an increasing relevance with regard to early and differential diagnosis of PD is stated. (ii) The categorization of dementia in the course of Parkinson’s disease. While there has been a clear separation between Parkinson’s disease and dementia with Lewy bodies so far, now a continuum is postulated which summarizes Parkinson’s disease without, with late and with early (within the first year after the occurrence of motor symptoms) dementia under the umbrella term of Lewy Body Diseases (LBD). (iii) The realization of a slowly spreading process of neurodegeneration occurring throughout different parts of the nervous system. This resulted in the definition of different phases of the disease, the preclinical, prodromal and clinical phase. In particular, the definition of the prodromal phase, characterized by different clinical parameters and further biomarkers still to be implemented, opens up new possibilities for early diagnosis and in the long run early treatment of Parkinson’s disease. (iv) The insight that the clinical phase is characterized by different forms of disease progression. For genetic variants (e. g., GBA or LRRK2) a separate clinical-genetic category is proposed, in idiopathic Parkinson’s disease subtypes should be characterized by clearly distinct prognosis, progression and/or treatment strategies. The MDS Task Force proposes to keep the current gold standard of typical clinical motor symptom presentation and post-mortem verification of α-synucleinopathy for the diagnosis of PD. The new clinical diagnostic criteria were designed using a typical clinical expert as benchmark, codifying the expert diagnostic process to make it reproducible and easily applicable. The new diagnostic criteria now contain absolute exclusion criteria, supportive criteria and “red flags” in addition to the assessment of the cardinal motor symptoms. Specific ancillary diagnostic tests (e. g., imaging techniques) can be implemented; furthermore the time course and severity of symptoms are taken into account.
Keywords: Parkinson’s disease; redefinition; clinical diagnostic criteria